Maqasid Sharia Perspective in Changes the Marriage Age Limits for Women According to Law Number 16 of 2019 - Rizki, Darlin; Oktalita, Frina; Sodiqin, Ali (Institut Agama Islam Negeri Curup, 2022)
This study analyzes the changes to Law no. 16 of 2019 on Law No. 1 of 1974 concerning the age limit of marriage. There are various responses in society, socio-cultural clashes and even religion cannot be avoided, where this situation is increasingly difficult to achieve the goal of marriage. This raises the question, why is it necessary to rearrange the age limits for marriage, and what background causes it? This study uses the maqasid sharia approach with the System theory of Jasser Auda. This type of research is descriptive qualitative using the maqasid sharia approach. The object of study is Law no. 19 of 2019 concerning Amendments to Law No. 1 of 1974 concerning Marriage. This study uses secondary data from two sources. First, the primary source is taken from the text of the Law and the Decision of the Constitutional Court. Second, secondary sources such as books, journals, reports, magazines, newspapers, and so on. Then the data are interpreted and analyzed descriptively. The results of this study showed that the determination of changes to the law regarding the age limit for marriage can be classified into the interests of al-dharurriyah (primary), which are important and must be fulfilled to achieve the goals of sharia, namely safety. The analysis of maqasid sharia with six subsystem features explains that protected interests are closely related, which are related to one another, representing age differences in marriage, which is a form of discrimination. The scope of the provisions on the age limit for marriage is classified as maqasid ‘ammah, because it covers all the interests of women in Indonesia. Also, as maqasid khassah, legal protection from the fulfillment of basic rights and constitutional rights as citizens. The level of dharuriyah does not always have the implication of obligatory syar'i (causing sin) but only until obligatory hukm (must), because the legal provisions are explored by mujtahids and are based on the absence of qat'y texts on this issue.